2016
DOI: 10.1111/1911-3846.12222
|View full text |Cite
|
Sign up to set email alerts
|

Budgeting in Times of Economic Crisis

Abstract: This article examines how corporate reliance on budgets is affected by major changes in the economic environment. We combine survey and archival data from the economic crisis that began in 2008. The results indicate that budgeting became more important for planning and resource allocation but less important for performance evaluation in companies affected more strongly by the 2008 economic crisis. Additional evidence from interviews and data gathered in a focus group further illustrate these results and show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(175 citation statements)
references
References 106 publications
7
124
1
17
Order By: Relevance
“…In this study, we concentrate on analyzing the impacts of three contingency variables on the research model parameters: Perceived Environmental Uncertainty (PEU), size, and strategy (e.g. Becker et al 2015). Previously, we have already shortly referred to the budgeting effects of PEU and strategy.…”
Section: Effect Of Contingency Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we concentrate on analyzing the impacts of three contingency variables on the research model parameters: Perceived Environmental Uncertainty (PEU), size, and strategy (e.g. Becker et al 2015). Previously, we have already shortly referred to the budgeting effects of PEU and strategy.…”
Section: Effect Of Contingency Variablesmentioning
confidence: 99%
“…Ezzamel (1990) showed that high PEU is associated with an emphasis on budgets for evaluation and required explanation of variances but also interactions between superiors and subordinates. Recently, Becker et al (2015) found that economic crisis in 2008 increased budgeting role in planning and resource allocation but decreased its role in performance evaluation. The budgets have been criticized that traditional budgets are even unsuitable for firms which have high uncertainty (see Frow et al 2010) because they may become quickly out of date (Libby and Lindsay 2010).…”
Section: Effect Of Contingency Variablesmentioning
confidence: 99%
“…It is important to notice, that budgeting became more important for planning and resource allocation, but less important for performance evaluation in companies effected more strongly by the 2008 economic crisis (Becker et al, 2016).…”
Section: Identifying Problemsmentioning
confidence: 99%
“…Nevertheless, recent studies of budgeting provide some evidence about the use of scenarios within planning and management control cycles. For example, Becker et al (2016) show that organisations develop scenarios in order to model the outcomes of different but likely future states of their business context and react quickly in case planning assumptions prove untrue in times of economic crisis. Henttu-Aho (2016) shows how, in a Finnish company that tried to alter the static nature of the budgeting process, controllers prepared alternative scenarios of the future state of affairs to support internal discussions.…”
Section: Scenarios In the Management Accounting Literaturementioning
confidence: 99%
“…Recent literature draws attention to the use of scenarios in planning and management control processes (Roche, 2010;Van der Stede and Palermo, 2011;Kaplan and Mikes, 2012;Merchant and Van der Stede, 2012;Becker et al, 2016;Henttu-Aho, 2016;Sponem and Lambert, 2016). Textbooks and professional articles describe scenarios and scenario analysis as the prospective analysis of multiple futures before the measurement of performances occurs (Roche, 2010;Van der Stede and Palermo, 2011;Merchant and Van der Stede, 2012).…”
Section: Introductionmentioning
confidence: 99%